Determinants of halal cosmetic purchasing decisions: The role of halal labels, product quality, price, and promotion (evidence from Viva Cosmetics consumers in Tulungagung Regency) - Mega Tunjung Hapsari; Sofiana Putri Nur Aini (Nur Science Institute, 2026)
The decision to purchase halal products is crucial, particularly given its relationship to consumers' religious beliefs and personal values. This study aims to comprehensively examine the influence of halal labeling, product quality, price, and promotion on halal cosmetic purchasing decisions in Tulungagung Regency. Using an associative quantitative approach, data were collected from 140 respondents selected through accidental sampling and analyzed using multiple linear regression. The findings reveal that all independent variables simultaneously significantly influence purchasing decisions. Partially, halal labeling, product quality, and promotion have a positive and significant effect, while price shows no significant influence. These findings imply that companies should prioritize maintaining credible halal certification, improving product quality, and designing innovative promotional strategies to strengthen consumer trust and purchasing decisions. This study contributes to the literature by providing empirical evidence on consumer behavior in the halal cosmetics sector at the regional level, particularly in emerging markets, thereby enriching the understanding of factors driving halal product consumption.